Freemasonry in Indonesia, 1942–1965: The Decline of the Organization during the Japanese Occupation and the Soekarno Administration - Solehudin Solehudin; Ajid Thohir; Usman Supendi (Swarnadwipa, 2026)
This study discusses the development and decline of Freemasonry in Indonesia from the Dutch East Indies colonial period to the administration of Soekarno. Freemasonry developed through Dutch colonial networks and exerted influence among the priyayi elite, intellectuals, and modern organizations such as Boedi Oetomo. This research employs a library research method by utilizing various historical sources, journals, archives, and official documents. The findings indicate that Freemasonry contributed to the development of modern thought and Western education in the Dutch East Indies, but it also generated controversy with Islamic organizations such as Sarekat Islam and Muhammadiyah, which viewed the organization as a threat to Islamic values and indigenous identity. The decline of Freemasonry began during the Japanese occupation in 1942, when the activities of Western organizations were restricted and their assets were confiscated. This condition continued during the administration of Soekarno, which strengthened nationalism, anti-colonialism, and the ideology of Pancasila through policies such as PEPERTI in 1961 and Presidential Decree Number 264 of 1962, which officially prohibited Freemasonry and its affiliated organizations in Indonesia.